2007
DOI: 10.1002/ange.200604344
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselektive und katalytische Reformatsky‐Reaktionen

Abstract: Modernisierte Klassiker: Kürzlich wurden bei der als Reformatsky‐Reaktion bekannten Kondensation von Aldehyden oder Ketonen mit α‐Halogencarbonylverbindungen beachtliche Fortschritte erzielt, zu denen unter anderem stereoselektive und katalytische Versionen gehören (siehe Schema, X=Halogen). Die zuverlässige Reaktion ist ideal für Synthesen im industriellen Maßstab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…[11] During this redox process, insertion of zinc into the halogen-carbon bond takes place forming a nucleophilic equivalent to a zinc enolate. Additionally, sponding aldol-Tishchenko products 5 in good yields.…”
Section: Introductionmentioning
confidence: 99%
“…[11] During this redox process, insertion of zinc into the halogen-carbon bond takes place forming a nucleophilic equivalent to a zinc enolate. Additionally, sponding aldol-Tishchenko products 5 in good yields.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In addition, many other metals have been considered in the Reformatsky-type reaction, and the corresponding enolates have been formed via transmetallation with alkylmetals or by the use of the metal in low oxidation state. [1,2] Recently, we have shown that an enantioselective Reformatsky reaction in the presence of a catalytic amount of metal complexes [8] or ligands, [9] could be effectively realized with a simple concept: performing the trasmetallation reaction between iodoacetate and Me 2 Zn in the presence of a chiral ligand able to control the mild formation of the enolate and its successive reaction with electrophiles. In this contribution, we report a practical and straightforward formation of zinc enolates promoted by air, their effective use in Reformatsky reactions with aldehydes and ketones, and preliminary results towards the development of the corresponding enantioselective variants.…”
mentioning
confidence: 99%
“…The Reformatsky reaction [1] represents a valuable tool for the synthetic chemist as it allows the facile addition of zinc enolates to aldehydes, ketones, or imines. [2] In general the reaction is heterogeneous, and efficient methodology has been introduced for the activation of the zinc.…”
mentioning
confidence: 99%
“…We speculated that moderation of the enolate reactivity might be necessary and screened Reformatsky reagents under standard conditions. [6][7][8] The use of zinc enolates in combination with the appropriate reaction temperature facilitated the development of a workable experimental protocol (Scheme 2). The hydroxysilane 8 was isolated as the predominant product when the reaction was conducted at À20 8C.…”
mentioning
confidence: 99%